CLINICAL AND HISTOPATHOLOGICAL CORRELATION IN TUBERCULOSIS OF SPINE BIOPSIES - Amin, Muhammad Shahbaz; Seema Butt; Abdullah Shahbaz; Majid Zaheer; Ashfaq Ahmed; Shazia Nilofer Ibnerasa (Journal of University Medical & Dental College, 2021)
ABSTRACT: BACKGROUND & OBJECTIVE: The tuberculosis (TB) of the spine is causing permanent deformities since long time. Earliest most possible accurate diagnosis is required to treat either TB or to exclude other lesions to avoid permanent disability. METHODOLOGY: This is a descriptive study conducted at pathology department of Lahore Medical & Dental College (LM&DC), Lahore from January 2017 to December 2019. All the spine biopsies received in Pathology department were included in the study irrespective of age and sex. Each biopsy was grossly and microscopically examined and reported by a histopathologist. RESULTS: Out of 386 specimens received, 189 (48.9%) were clinically diagnosed as tuberculosis. Out of these 189 cases, 127 were confirmed on histopathological examination showing clinicopathological correlations in 67.19 % of cases. The rest 62 (32.80%) of the cases were reported as chronic non specific inflammation (38), degenerative changes (11), metastatic tumor (04), and atypical cell infiltrate (02), plasma cell neoplasm (01), Non Hodgkin Lymphoma (01) and other lesions (05) which all were benign. Out of the total 386 spine biopsies, 154 (39.89 %) were histopathologically proven for tuberculosis. From these 154 histologically proven cases, 127 were clinically suspected cases of Tuberculosis. No clinical diagnosis was provided in 02 patients. The rest of 25 patients were clinically labeled as pathological lesion without specific diagnosis. CONCLUSION: Histopathology should be considered as the most reliable tool for spinal tuberculosis to minimize permanent disability associated with wrong management based on potentially erroneous clinical diagnosis.